LcNAC13 Is Involved in the Reactive Oxygen Species-Dependent Senescence of the Rudimentary Leaves in Litchi chinensis - Wang, Congcong; Liu, Hao; Huang, Lijie; Chen, Houbin; Lu, Xingyu; Zhou, Biyan (Frontiers in Plant Science, 2022)
Litchi is an important evergreen fruit tree. Floral formation in litchi is induced by low temperatures (LTs). However, unstable flowering is a challenge for litchi production in times of global warming and climate change. Previous studies have shown that the methyl viologen dichloride hydrate-generated reactive oxygen species (ROS) could promote flowering. Leaves in the panicles may affect the development of the inflorescence in litchi under high-temperature condition. In this study, potted litchi trees were transferred to growth chambers at LT and high temperature (HT). From a previous dataset of the RNA sequencing of the ROS-treated rudimentary leaves, a NAC transcription factor-encoding gene LcNAC13 was identified. By genetic transformation of LcNAC13 to Arabidopsis thaliana and tobacco, it was found that the ROS-induced senescence of the leaves was accelerated. Silencing LcNAC13 by virus-induced gene silencing (VIGS) delayed ROS-dependent senescence. Our results suggested that LcNAC13 regulates rudimentary leaf senescence. Our study provided a new target gene for the future molecular breeding of new cultivars that could flower under global warming conditions.